The Need for Better Monitoring of Climate Change in the Middle and Upper Atmosphere - Juan A. Añel; Ingrid Cnossen; Juan Carlos Antuña‐Marrero; Gufran Beig; Matthew K. Brown; Eelco Doornbos; Scott Osprey; Shaylah Maria Mutschler; Celia Pérez Souto; Petr Šácha; Viktoria Sofieva; Laura de la Torre; et al. (AGU Advances)
Abstract Anthropogenic greenhouse gas emissions significantly impact the middle and upper atmosphere. They cause cooling and thermal shrinking and affect the atmospheric structure. Atmospheric contraction results in changes in key atmospheric features, such as the stratopause height or the peak ionospheric electron density, and also results in reduced thermosphere density. These changes can impact, among others, the lifespan of objects in low Earth orbit, refraction of radio communication and GPS signals, and the peak altitudes of meteoroids entering the Earth's atmosphere. Given this, there is a critical need for observational capabilities to monitor the middle and upper atmosphere. Equally important is the commitment to maintaining and improving long‐term, homogeneous data collection. However, capabilities to observe the middle and upper atmosphere are decreasing rather than improving.